Use of low pressure mercury lamps with H2O2 and TiO2 for treating carbamazepine in drinking water: Batch and continuous flow through experiments. (December 2018) - Somathilake, Purnima; Dominic, John Albino; Achari, Gopal; Langford, Cooper H.; Tay, Joo-Hwa
Abstract: This study evaluated advanced oxidation processes that use germicidal low pressure (LP) mercury lamps to identify an energy efficient treatment technology that can degrade carbamazepine (CBZ) in drinking water. In this context, degradation of carbamazepine in deionised water by direct photolysis (UVC, λ = 254 nm), UVC/H2 O2 and UVC/TiO2 were investigated using batch and flow through experiments. Batch experiments were conducted to determine the degradation kinetics of CBZ spiked in deionised water under varying UV intensities and chemical doses. Effect of incidental UV intensity was studied under 0.6, 2.2 and 3.4 kW/m 3 and H2 O2 doses were varied between 10 to 100 mg/L. Effect of TiO2 was studied using 0.5, 1.0 and 1.5 g/L Degussa P25. Among all the combinations, CBZ degraded rapidly under UV intensity of 3.4 kW/m 3 in the presence of 50 mg/L of H2 O2 . The effect of various parameters on degradation of CBZ was further described by developing relationships equating operational parameters and kinetic coefficients. These relationships were validated with kinetic coefficients estimated from continuous flow through experiments. Kinetic constants obtained for optimal conditions under flow through experiments were in good agreement with the equation developed and had a marginal deviation of only 6%. Energy requirements for direct photolysis and UVC/TiO2 under optimal conditions were 380 and 8 times higher than for UVC/H2 O2 .